1986
DOI: 10.7557/2.6.1-app.579
|View full text |Cite
|
Sign up to set email alerts
|

Radiocesium concentrations in the lichen-reindeer/caribou food chain: Before and after Chernobyl

Abstract: This paper reviews historical concentrations of radiocesium (Cs-137) in the reindeer/caribou food chain in Alaska. These data, along with available kinetic models which describe the movement of radiocesium through the food chain, are used to predict consequences of radioactive fallout from the Chernobyl accident which occurred in late April 1986. During the present discussion, efforts are made to directly relate the Alaskan data to the Scandinavian situation as it exists following the Chernobyl accident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
(8 reference statements)
2
8
1
Order By: Relevance
“…Taylor et al (1988) reported a 19% average increase of 137 Cs concentrations in mosses and lichens in Canada as a result of the deposition from Chernobyl. This increase is much lower than that observed in some Alaskan lichens (White et al, 1986), as mentioned above, but slightly higher than those of lichen in Illutalik (5%) and Skarvefjeld (10%) in the present study. If only the top parts of the lichens are compared, the increase due to the Chernobyl deposition is likely to be much higher, because the contribution from weapon fallout is situated in the older basal parts of the lichen thallus.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Taylor et al (1988) reported a 19% average increase of 137 Cs concentrations in mosses and lichens in Canada as a result of the deposition from Chernobyl. This increase is much lower than that observed in some Alaskan lichens (White et al, 1986), as mentioned above, but slightly higher than those of lichen in Illutalik (5%) and Skarvefjeld (10%) in the present study. If only the top parts of the lichens are compared, the increase due to the Chernobyl deposition is likely to be much higher, because the contribution from weapon fallout is situated in the older basal parts of the lichen thallus.…”
Section: Discussioncontrasting
confidence: 75%
“…White et al (1986) compared the 137 Cs level in lichens and vascular plants on selected sites in Alaska before and after the Chernobyl accident. In some lichens from these sites, a 75% increase was observed, while in some vascular plants the increase was 120%.…”
Section: Discussionmentioning
confidence: 99%
“…The Cs concentrations ranged from 2.1 to 44.0 Bq/kg, with a geometric mean of 7.3 Bq/kg, in the soil samples and from 16.3 to 24.2 Bq/kg, with a geometric mean of 59.9 Bq/kg, in lichen samples. This range of 137Cs concentration is comparable to the range of 59-181 Bq/kg reported earlier for lichens in the study area just before the Chernobyl accident (Hanson, 1982;White et al, 1986). However, the mean concentration (59.9 Bq/kg) of our arctic lichen samples is much lower than the values (approximately 600 Bq/kg) expected from the physical decay of 37Cs for the values reported between 1962 and 1968 (925-1100 Bq/kg).…”
supporting
confidence: 89%
“…There has been a gradual decrease in bioavailable radiocesium since the cessation of atmospheric weapons testing; thus for Alaska, radiocesium concentrations in lichen, caribou and reindeer have decreased from peak concentrations of 1200-1800 Bq/kg in the mid-1960s to less than 300 Bq/kg in January 1986 (White et al, 1986). The total amount of radiocesium discharged into the atmosphere following the Chernobyl accident on 26 April 1986 was at most 510% of the total amount of radiocesium released from all atmospheric nuclear weapons tests (Goldman, 1987).…”
Section: )mentioning
confidence: 99%
“…White et al (1986) predicted inputs as high as 75% of the 137 Cs in Alaska to be deposited from the nuclear accident; however, there is little evidence of similar high contributions in either the woodland or barren ground herds in the Yukon. The higher inputs are probably the result of much lower 137 Cs concentrations in Alaskan caribou at that time, making the input after the Chernobyl accident large by comparison.…”
Section: Discussionmentioning
confidence: 99%